Phrathammanūn Sān Yuttitham. - Sūtphaisān (Firm) (Krung Thēp : Samnakphim Sūtphaisān, 2006)
Commentary on constitutional law concerning court of justice of Thailand.
[v. 1] Phrathammanūn sān yuttitham chabap sombūn Phō̜.Sō̜. 2545-2548: [1.1.] Ratthathammanūn hǣng Rātchaʻānačhak Thai "chapho̜ wādūai sān læ sān yuttitham" plǣ Thai-ʻAngkrit -- [1.2.] Phrathammanūn sān yuttitham -- [1.3.] Kānwinitchai chīkhāt ʻamnāt nāthī rawāng sān -- [1.4.] Rabīap bō̜rihān rātchakān sān yuttitham -- [1.5.] Rabīap khārātchakān fāi tulākān sān yuttitham læ khō̜ bangkhap rabīap prakāt thī samkhan tām phrarātchabanyat -- [v. 2] Phrathammanūn sān yuttitham lem 2 phrō̜m CD: [2.1.] Phrathammanūn sān yuttitham 2543 -- [2.2.] Phatthanākān bō̜rihān ngānyuttitham hǣng chāt 2549 -- [2.3.] Rabīap bō̜rihān rātchakān sān yuttitham 2543 -- [2.4.] Rabīap khārātchakān fāi tulākān sān yuttitham 2543 -- [2.5.] Kānwinitchai chīkhāt ʻamnāt nāthī rawāng sān 2542 -- [2.6.] Yok thāna sān khw̄ǣng-- pen sān čhangwat 2549 -- [v. 3] Phrathammanūn sān yuttitham lem 3: plǣ Thai-ʻAngkrit = Law for the organizarion of Court of Justice: translated Eng-Thai.
In Thai and English.
Keywords: Courts -- Thailand; Constitutional law -- Thailand